Interpretation of Fundamental Rights in Slovakia - Šmigová, Katarína (Constitutional Reasoning and Constitutional Interpretation: Analysis on Certain Central European Countries, 2021)
This chapter aims to analyze the jurisprudence of the Constitutional Court of the Slovak Republic (hereinafter the ‘Constitutional Court’) and related case-law of the European Court of Human Rights (hereinafter also ‘the Court’ or ‘the ECtHR’) within the framework of the Interpretation of Fundamental Rights in Europe project. It is divided into five subchapters. The first presents the position and competence of the Constitutional Court of the Slovak Republic and discusses basic features of its proceedings compared to ECtHR proceedings. The second subchapter explains the status of the Convention on Human Rights and Fundamental Freedoms within the Slovak legal order and the status of the Convention as an international treaty. Both issues are important in relation to the opinion of the Constitutional Court and the Court on the matter of interpretation as such that is analyzed and compared within the third subchapter. The fourth and fifth subchapters begin with a presentation of the selection criteria of decisions of the Constitutional Court and the Court, respectively, which are subsequently analyzed and compared in relation to the methods of interpretation. The conclusion summarizes the result that both courts use similar interpretative methods, but not to a similar extent. Moreover, there are certain differences that originate qualitatively from the position of these courts within the system of judicial bodies and quantitatively from the selection criteria since the selection of the decisions of the Court has been fundamentally influenced by the selected decisions of the Constitutional Court.